CHARACTERISTICS OF SELF-ATTITUDE IN ADOLESCENT PERIOD (Proceedings of International Educators Conference, 2024)
The article aims to determine the place of psychological factors influencing the formation of self-relation during adolescence. According to him, the analyzes of scientists regarding the formation of self-relation during adolescence are described. In particular, the manifestation of self-relation in the adolescent personality is highlighted on the basis of empirical research.